2016
DOI: 10.18632/oncotarget.12695
|View full text |Cite
|
Sign up to set email alerts
|

Properdistatin inhibits angiogenesis and improves vascular function in human melanoma xenografts with low thrombospondin-1 expression

Abstract: In this study, the effect of properdistatin, a novel peptide derived from the thrombospondin 1 (TSP-1) domain of properdin, was investigated in three melanoma xenograft models with different TSP-1 expression. The tumors were grown in dorsal window chambers and were treated with 80 mg/kg/day properdistatin or vehicle. Morphological parameters of the tumor vasculature were assessed from high resolution transillumination images. Blood supply time (i.e., the time required for arterial blood to flow from a supplyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the present study, we first demonstrated that RSV-activated MGCs showed increased expression of the antiangiogenic factors, PEDF and TSP-1, as well as the phagocytic ability. PEDF is well known to reduce migration and promote apoptosis of endothelial cells [ 21 ], and TSP-1 induces apoptosis of endothelial cells and prevents them from responding to a wide variety of angiogenic stimulators [ 22 ]. While MCGs are known to express PEDF and TSP-1 under normal conditions [ 6 ], we demonstrated that RSV treatment upregulated PEDF and TSP-1 expression, and may have anti-CNV properties.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we first demonstrated that RSV-activated MGCs showed increased expression of the antiangiogenic factors, PEDF and TSP-1, as well as the phagocytic ability. PEDF is well known to reduce migration and promote apoptosis of endothelial cells [ 21 ], and TSP-1 induces apoptosis of endothelial cells and prevents them from responding to a wide variety of angiogenic stimulators [ 22 ]. While MCGs are known to express PEDF and TSP-1 under normal conditions [ 6 ], we demonstrated that RSV treatment upregulated PEDF and TSP-1 expression, and may have anti-CNV properties.…”
Section: Discussionmentioning
confidence: 99%
“…However, the functional implication of this structural division of disulfide connectivity is as yet unclear, even though Tan et al (2002) originally suggested that the division of the top disulfide also divides the effect on angiogenesis. It still appears to be true that several proteins from the Cys 1 -Cys 4 disulfide group, including CCN proteins, spondins and HB-GAM, simulate angiogenesis (Kazanskaya et al, 2008;Papadimitriou et al, 2016;Kubota & Takigawa, 2007), while the Cys 3 -Cys 4 group, including thrombospondins, Unc5, properdins, ADAMTS proteins and papillin, inhibit angiogenesis (Lawler & Lawler, 2012;Larrivé e et al, 2007;Gaustad et al, 2016;Sun et al, 2015;Karagiannis & Popel, 2007). However, knowledge of more proteins with known functions from each group, and ideally complex structures with ligands bound differently owing to the different top disulfide, are needed before we can make a reliable statement regarding the correlation, if any, between the disulfide group and the functionality.…”
Section: Similarity and Diversity In Tsp1 Domainsmentioning
confidence: 99%
“…This function is mainly meditated through the TSRs, which bind to the CLESH domain of CD36 and to β1 integrins. The importance of the anti-angiogenic activity of the TSRs is underscored by the fact that other proteins that contain TSRs also have anti-angiogenic activity (Gaustad et al 2016). Engagement of α5β1 integrin by 3TSR inhibits endothelial cell migration in a PI3K-dependent manner (Short et al 2005) (Fig.…”
Section: Inhibition Of Angiogenesis By Tsp-1mentioning
confidence: 99%